Antenatal exposure to antidepressant drugs and the risk of neurodevelopmental and psychiatric disorders: a systematic review - Jessica Salvador Areias de Araujo; Isabella Fernandes Delgado; Francisco José Roma Paumgartten
Abstract: This study investigated whether antenatal exposure to antidepressants (ADs) increases the risks of autism spectrum disorders (ASD), attention deficit/hyperactivity disorders (ADHD), schizophrenia and other mental illnesses, and cognitive and developmental deficits in infants or preschool children. PubMed, EMBASE, BIREME/BVS databases were searched to identify studies examining associations of ADs in pregnancy with neurodevelopmental and psychiatric disorders. Twenty studies addressed ASD and/or ADHD risks while 30 focused on developmental and cognitive deficits in infants or preschool children. Most studies detected no association of antenatal AD with ASD after adjustment of risk ratios for maternal depression or psychiatric disorders. Some studies showed that maternal depression, regardless of whether it is treated or untreated, increased ASD risks. Seven out of 8 studies found no increase in ADHD risk associated with antenatal exposure to selective serotonin reuptake inhibitors, the most commonly used AD. No consistent evidence was found linking AD in pregnancy to neurocognitive developmental deficits in infants or preschool children. A residual confounding by indication (depression severity) remained in almost all studies. This systematic review found no consistent evidence suggesting that ADs in pregnancy increase risks of ASD, ADHD, and neurocognitive development deficits. Some studies, however, found evidence that maternal depression increases ASD risks.